2017
DOI: 10.18632/oncotarget.18630
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin-1 is a glial cell line-derived neurotrophic factor receptor in glioblastoma

Abstract: The aim of this study was to identify the receptor for glial cell line-derived neurotrophic factor (GDNF) in glioblastoma multiforme (GBM). After GST pull-down assays, membrane proteins purified from C6 rat glioma cells were subjected to liquid chromatography-tandem mass spectrometry (LC-MS/MS). The differentially expressed proteins were annotated using Gene Ontology, and neuropilin-1 (NRP1) was identified as the putative GDNF receptor in glioma. NRP1 was more highly expressed in human GBM brains and C6 rat gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 56 publications
1
23
0
2
Order By: Relevance
“…Previous studies have shown that the expression of GDNF in human glioblastoma is significantly increased compared to normal brain tissues [ 9 , 21 ]. Additionally, it has been reported that GDNF participates in regulating the proliferation, migration, and invasion of glioblastoma cells [ 9 , 10 , 22 , 23 ]. It is also well known that VEGF plays an important role in neovascularization in brain tumors [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the expression of GDNF in human glioblastoma is significantly increased compared to normal brain tissues [ 9 , 21 ]. Additionally, it has been reported that GDNF participates in regulating the proliferation, migration, and invasion of glioblastoma cells [ 9 , 10 , 22 , 23 ]. It is also well known that VEGF plays an important role in neovascularization in brain tumors [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cytoplasmic and nuclear protein extraction reagents (Beyotime) with PMSF were used for the extraction of nuclear and cytoplasmic fractionations as described by the manufacturer. For co-Immunoprecipitation, lysates were extracted with IP buffer and carried out as previously described [31].…”
Section: Real-time Quantitative Pcrmentioning
confidence: 99%
“…Post-translational modifications such as phosphorylation may modulate nuclear import rates, e.g., phosphorylation of adjacent Ser111/112 N-terminal to the NLS of SV40T antigen greatly enhances its nuclear import [41]. We had previously reported that GDNF contributes to glioma progression [2,31], while GDNF has also been linked to the activation of kinases in favor of glioma [42]. We asked if GDNF can promote DCX phosphorylation and subsequently affect nuclear import.…”
Section: High Gdnf Expression Promotes DCX Nuclear Importmentioning
confidence: 99%
“…As Sema3C signaling has been implicated in GSC maintenance, we will focus our discussion on its receptors in glioblastoma. Elevated Nrp1 expression is a risk factor for glioblastoma recurrence and shorter patient survival [ 75 ]. Disruption of Nrp1 signaling by siRNA knockdown significantly inhibits proliferation of glioma cell lines [ 76 ] phenocopying Sema3C knockdown.…”
Section: Sema3c Receptors In Carcinogenesismentioning
confidence: 99%